Clinical research on the effectiveness and safety of Uchasingihwan for low back pain with radiculopathy caused by herniated intervertebral disc of the lumbar spine: A multicenter, randomized, controlled equivalence trial - Bonhyuk Goo; Jung-Hyun Kim; Eun-Jung Kim; Dongwoo Nam; Hyun-Jong Lee; Jae-Soo Kim; Yeon-Cheol Park; Yong-Hyeon Baek; Sang-Soo Nam; Byung-Kwan Seo (Integrative Medicine Research)
Background: This study aimed to establish the clinical evidence regarding the effectiveness and safety of Uchasingihwan (UCSGH) in improving pain, function, and quality of life in patients with lumbar herniated intervertebral disc (LHIVD). Methods: This was a multicenter, randomized, controlled, equivalence trial with two parallel arms. Seventy-four participants with LHIVD were recruited and randomly allocated to the experimental and control groups. The participants in each group took 2.5 g of UCSGH granule or loxoprofen 60 mg tablet three times a day for six weeks. Additionally, both groups received the same acupuncture treatment once a week for six weeks. Outcomes about effectiveness and safety were assessed at baseline and 3, 6, and 10 weeks after screening. Results: As the primary outcome, the mean differences with a 95 % confidence interval (CI) of changes in low back pain between the two groups at weeks 6 (95 % CI:9.26, 8.37) and 10 (95 % CI:9.03, 9.62) from baseline were within the equivalence limit. Also, changes in radiating pain at weeks 6 (95 % CI:1.70, 15.69) and 10 (95 % CI:4.72, 13.75) were within the equivalence limit. Outcome measures for function and quality of life also showed no statistical difference. Regarding safety, the frequency of adverse events related to intervention was lower in UCSGH. Conclusion: UCSGH showed the equivalent level of effectiveness as loxoprofen in reducing low back and radiating pain in LHIVD patients and showed sufficient safety to be used as a complementary treatment option. Trial registration: ClinicalTrials.gov (NCT03386149), CRIS (KCT0002848).